PERSEPSI GURU PJOK SEKOLAH MENENGAH PERTAMA DI NANGA PINOH TERHADAP KURIKULUM MERDEKA - Mutaqin, Nur Sulistyo; Rudiansyah, Eko (STKIP Melawi, 2025)
Abstract: The researcher aims to explore teacher perceptions of the implementation of the Merdeka Curriculum in Junior High Schools (SMP) in Nanga Pinoh District. This research is a descriptive qualitative research with the Survey method. The subjects of this study were 8 junior high school Physical Education, Sports and Health (PJOK) teachers in Nanga Pinoh District with Purposive Sampling. Using questionnaire, interview, and documentation data collection techniques. Data analysis used in this research is data reduction, data display, conclusion/verification. The results of the questionnaire to 8 respondents received a good score with a percentage of 87.5% in the very good category with a percentage of 12.5% so that the teacher's perception of Merdeka learning in junior high schools in Nanga Pinoh District was in the good category.Keywords: Teacher perceptions, physical education, Merdeka Curriculum Abstrak: Peneliti bertujuan untuk menggali persepsi guru terhadap implementasi Kurikulum Merdeka di Sekolah Menengah Pertama (SMP) se Kecamatan Nanga Pinoh. Penelitian ini merupakan penelitian kualitatif deskriptif dengan metode Survei. Subjek penelitian ini adalah Guru Pendidikan Jasmani Olahraga dan Kesehatan (PJOK) tingkat SMP di Kecamatan Nanga Pinoh yang berjumlah 8 orang dengan Purposive Sampling. Menggunakan teknik pengumpulan data kuesioner, wawancara, dan dokumentasi. Analisis data yang digunakan dalam penelitian ini adalah reduksi data, display data, kesimpulan/verifikasi. Hasil dari kuesioner terhadap 8 responden mendapatkan nilai baik dengan persentase 87,5 % berada dalam kategori sangat baik dengan persentase 12,5% sehingga persepsi guru terhadap Merdeka belajar di SMP se Kecamatan Nanga Pinoh berada di kategori baikKata kunci: Persepsiiguru, PJOK,iKurikulumiMerdeka